Perbedaan Tingkat Self Regulated Learning Siswa Sekolah Menengah Pertama di Masa Pandemi Ditinjau Dari Jenis Kelamin - Istiqomah, Intan Wahyu; Faruq, Faruq; Sabani, Nureyzwan; Rahmawati, Siti; Rivalna, Kelvin; Kumaidi, K; Sudinadji, Muh Bagus (Prosiding University Research Colloquium, 2021)
This study aims to identify the level of self-regulated learning of male and female students in junior high schools (SMP) in the residency of Surakarta. This quantitative study involved 223 students consisting of 115 male students and 108 female students as the research subjects. The instrument used is the Self-regulated Learning Scale which was developed based on aspects of Zimmerman’s theory with the results of the validity test using a CVI of 0.68 to 1.00 and a reliability test with a Cronbach alpha value of 0.893. The data analysis method used in this study is Non Parametric with the Mann-Whitney Test. The results showed that there was a significant difference between the self-regulated learning of male students and female students during the pandemic period, the self- regulated learning of female students was higher than male students.